Analysis of referral marketing implementation in increasing online sales - Batlajery, Semuel; Longgy, Dodhy Hyronimus Ama; Adiatma, Tini; Alfons, Marlyn E. (Privietlab, 2026)
This study aims to examine the implementation of referral marketing in increasing online sales in a social-media-based online retail business. A qualitative approach was employed to gain an in-depth understanding of how referral marketing operates in practice and how it contributes to sales growth. Data were collected through observation, in-depth interviews, and documentation, involving five informants selected through purposive sampling. The data were analyzed using the interactive model of Miles and Huberman, which consists of data reduction, data display, and conclusion drawing/verification. The findings show that referral marketing was implemented through a structured mechanism involving referral links, discounts, reward points, and purchase credits. Its effectiveness was further supported by the use of digital platforms such as Instagram, WhatsApp, Facebook, and TikTok, which enabled recommendations to spread more quickly and personally. The study also found that recommendations from friends and family were perceived as more credible than conventional promotional messages, thereby strengthening trust, encouraging new customer acquisition, increasing repeat purchases, and supporting customer loyalty. In addition, referral marketing was perceived as relatively cost-efficient because incentives were only provided when successful transactions occurred. Therefore, referral marketing can be understood as an effective relational digital strategy for supporting online sales growth.